2020
DOI: 10.1038/s41419-020-03245-8
|View full text |Cite
|
Sign up to set email alerts
|

Neurotensin pathway in digestive cancers and clinical applications: an overview

Abstract: Initially, NEUROTENSIN (NTS) has been shown to play physiological and biological functions as a neuro-transmitter/modulator in the central nervous system and as an endocrine factor in the periphery, through its binding to two kinds of receptors: NTSR1 and 2 (G protein-coupled receptors) and NTSR3/sortilin (a vacuolar protein-sorting 10-domain receptor). NTS also plays oncogenic roles in many types of cancer, including digestive cancers. In tumor tissues, NTS and NTSR1 expression is higher than in healthy ones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 104 publications
1
30
0
Order By: Relevance
“…Studies in mice showed that hepatic sortilin overexpression reduced the production of Apolipoprotein B (ApoB) [37]; Mechanistically, Amengual et al found that autophagy is required for SORT1-mediated degradation of ApoB [38]. In addition, sortilin recently emerged as a promising tumor target as its expression was found to be increased in several types of cancers including digestive cancers [39][40][41], but its expression and impact in GC is unclear. Autophagy is a highly conserved intracellular homeostasis mechanism through which cellular material is delivered to lysosomes for degradation, resulting in the basal turnover of cell components and providing energy and macromolecular precursors.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in mice showed that hepatic sortilin overexpression reduced the production of Apolipoprotein B (ApoB) [37]; Mechanistically, Amengual et al found that autophagy is required for SORT1-mediated degradation of ApoB [38]. In addition, sortilin recently emerged as a promising tumor target as its expression was found to be increased in several types of cancers including digestive cancers [39][40][41], but its expression and impact in GC is unclear. Autophagy is a highly conserved intracellular homeostasis mechanism through which cellular material is delivered to lysosomes for degradation, resulting in the basal turnover of cell components and providing energy and macromolecular precursors.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that neuropeptides in a variety of tumor systems may be regulated by exosomes and that abnormalities in such regulation can affect neuroendocrine function [ 15 17 ]. Exosomes are membrane-bound vesicles that can transport biologically active molecules between cells [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with solid tumours that originate from these organs tend to have higher morbidity and mortality compared with other organ systems (7). Previous studies have shown that there are common intersections between tumorigenesis mechanisms and regulatory networks in different digestive cancers (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%